(untitled) (Heritage, 2022)
The motif of a single-headed and double-headed eagle first appeared in Serbian medieval art under the influence of the Byzantine Empire or Christian tradition. This motif was used by the Byzantine Empire as a symbol of royal dignity and as a representation of saints. Since the eagle is regarded as a symbol of Jesus Christ, the resurrection, the Holy Evangelist John, and etc, Christian influence is more visible in literature. The use of the eagle as a motif in Raška was heightened during Grand župan Stefan Nemanja’s reign and continued through his successors. Studenica monastery depicts both single-headed and double-headed eagle motifs. A single-headed eagle is a fresco painted in a double circle, and a double-headed eagle is a fresco painted as kolasta azdija, which represents a motif of golden double-headed eagles in double circles. Kolasta azdija can be found on the gowns of King Stefan the First-Crowned and his son King Radoslav in the Žiča monastery. A motif of a red double-headed eagle was also used as a decorative element of the St. George’s wall and cloak. At Mileševa monastery, golden encircled double-headed eagles adorned the gowns of King Stefan the First-Crowned and his sons Radoslav and Vladislav. The motif of single-headed eagles in circles can be found as a unique example on Knez Stefan’s gown in the Morača monastery. An eagle can be found as a motif in manuscripts, on the seal, and as part of the church’s interior decoration. During King Uroš I and his successors’ reigns, double-headed eagles vanished as a symbol of royal dignity, but they remained as a Christian symbol until the end of the XIII century.